2017
DOI: 10.1007/s10072-017-2920-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Wi-Fi electromagnetic waves in unimodal and multimodal object recognition tasks in male rats

Abstract: Wireless internet (Wi-Fi) electromagnetic waves (2.45 GHz) have widespread usage almost everywhere, especially in our homes. Considering the recent reports about some hazardous effects of Wi-Fi signals on the nervous system, this study aimed to investigate the effect of 2.4 GHz Wi-Fi radiation on multisensory integration in rats. This experimental study was done on 80 male Wistar rats that were allocated into exposure and sham groups. Wi-Fi exposure to 2.4 GHz microwaves [in Service Set Identifier mode (23.6 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…3) Test phase; after 45 min, the rats were replaced in the arena which contained one familiar and one novel object for a period of 3 min. Discrimination ratio (as recognition index) was defined as ratio of time spent for exploring each object to the total time spent for exploring both the objects in the training and test phases [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…3) Test phase; after 45 min, the rats were replaced in the arena which contained one familiar and one novel object for a period of 3 min. Discrimination ratio (as recognition index) was defined as ratio of time spent for exploring each object to the total time spent for exploring both the objects in the training and test phases [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it may lead to adverse effects, such as neurodegenerative diseases, originating from changes in miRNA expression. In an animal study, Hassanshahi et al [16] demonstrated that Wi-Fi radiation had possible adverse effects on cross-modal and unimodal novel object recognition. An important issue is the level of RF exposure from Wi-Fi in schools and public areas [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Testylier et al found that the Ach released in the hippocampal CA1 area decreased after 1 h of microwave radiation exposure with 2.45 GHz and 4 mW/cm 2 , and the extracellular Ach concentration reached the lowest level of approximately 60% pre-exposure at 6 h after radiation (28). Other studies have shown that the M1 type of AChR is upregulated, the activity of AChE is increased, and the intracellular calcium concentration is increased in the hippocampus after long-term and low-dose microwave radiation at 2.45 GHz (44,70). Derin et al arranged Wistar rats into a sham-exposed group and 45 and 65 V/m exposed groups; the exposure group experienced 1 week of exposure at a frequency of 2.1 GHz.…”
Section: Effects Of Emr On Acetylcholine (Ach)mentioning
confidence: 93%